1992
DOI: 10.1002/cm.970210109
|View full text |Cite
|
Sign up to set email alerts
|

Trout sperm swimming patterns and role of intracellular Ca++

Abstract: We investigated the swimming patterns of trout sperm using computer-assisted analyses of video microscopy. Under full activation conditions, in which 80-100% of sperm activate their motility, sperm swim in circular paths for 2-5 sec, followed by 30-60 sec of a more linear swimming, and, finally, cessation of movement, with a straightening of the flagella. Threshold activation, in which 50% of the sperm activate, is characterized by circular patterns of swimming for less than 20 sec, with straightened flagella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
73
0
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 30 publications
5
73
0
1
Order By: Relevance
“…It was also shown by Okuno and Morisawa (32) that demembranated trout sperm showed vigorous motility in the reactivating solution containing Ca 2ϩ in a concentration below 10 Ϫ8 M, suggesting that the initiation of fish sperm motility requires a transient influx of Ca 2ϩ , although its origin, from intracellular storage or of extracellular origin, is controversial (29). The present results suggest that the presence of extracellular Ca 2ϩ is necessary for the initiation of sperm motility in carp.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…It was also shown by Okuno and Morisawa (32) that demembranated trout sperm showed vigorous motility in the reactivating solution containing Ca 2ϩ in a concentration below 10 Ϫ8 M, suggesting that the initiation of fish sperm motility requires a transient influx of Ca 2ϩ , although its origin, from intracellular storage or of extracellular origin, is controversial (29). The present results suggest that the presence of extracellular Ca 2ϩ is necessary for the initiation of sperm motility in carp.…”
Section: Discussionsupporting
confidence: 67%
“…An increase in intracellular calcium is a prerequisite for the initiation of sperm motility in rainbow trout (28)(29)(30)(31). It was also shown by Okuno and Morisawa (32) that demembranated trout sperm showed vigorous motility in the reactivating solution containing Ca 2ϩ in a concentration below 10 Ϫ8 M, suggesting that the initiation of fish sperm motility requires a transient influx of Ca 2ϩ , although its origin, from intracellular storage or of extracellular origin, is controversial (29).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Krasznai et al (8) demonstrated that the activation of voltagegated calcium channels is required in carp sperm for motility initiation; this activation depends upon membrane hyperpolarization through opening of K ϩ channels and a K ϩ efflux. In other teleosts, there has been debate over the source of the Ca 2ϩ and thus the need for Ca 2ϩ channels during the [Ca 2ϩ ] i increase at motility initiation (36). Although some studies have suggested that Ca 2ϩ from intracellular stores may be sufficient for motility initiation (36) or may participate in the initiation of motility as has been described in puffer fish (9), most studies have suggested that it is the influx of external Ca 2ϩ after membrane hyperpolarization that is required for motility (5,8).…”
Section: Discussionmentioning
confidence: 99%
“…In salmonids, motility initiation occurs with dilution in freshwater, specifically from a reduction in extracellular potassium that drives a membrane hyperpolarization and an increase in intracellular calcium ([Ca 2ϩ ] i ) (2)(3)(4)(5)(6). Changes in the concentrations of specific ions (Ca 2ϩ , K ϩ , and possibly Na ϩ and Cl Ϫ ) also have been linked to motility initiation in Atlantic croaker sperm (7).…”
mentioning
confidence: 99%